(untitled) (Fiep Bulletin - online, 2014)
This research aimed to investigate the presence of classes in classical ballet training program of athletes Gymnastics during the execution of a series of soil and check for possible relationships between the practice of classical ballet and performance of the gymnasts during the execution of a number of soil. Data collection was carried out during the conference coach of Brazil Gymnastics Trophy and 1st stage circuit box artistic gymnastics and rhythmic gymnastics held in Campo Grande . The instrument used for data collection was questionnaire consisting of seven questions closed with two scopes : the training of gymnastics and the people responsible for the ballet lessons . The sample was composed of 11 technical artistic gymnastics . The results of this research showed that most athletes train more than 20 hours and of these only two hours are dedicated to artistic preparation including classical ballet and classical ballet can contribute to posture , lightness , aesthetics , correction of movements and body language , which enhances the presentation.